Ferrocene-contained metal organic frameworks: From synthesis to applications - Huang, Zhikun; Yu, Haojie; Wang, Li; Liu, Xiaowei; Lin, Tengfei; Haq, Fazal; Vatsadze, Sergey Z.; Lemenovskiy, Dmitry A. (Coordination chemistry reviews, 2021)
•The Fc-contained MOFs was first reviewed.•The Fc-contained MOFs can be clearly divided into four basic categories.•The synthesis methods of Fc-contained MOFs and their corresponding applications were reviewed.•The challenges and further research directions of Fc-contained MOFs were presented. Recently, metal organic frameworks (MOFs) have attracted tremendous research attention in many fields, including gas separation, wastewater treatment, energy storage and conversion, catalysis, sensors, etc. To satisfy various demands of special practical applications, the pristine MOFs were usually hybridized with other molecules to form multifunctional materials. Due to their unique reversible redox properties, outstanding optical and electrochemical activities, ferrocene (Fc) and its derivatives have been employed as the guest molecules or functional units in MOFs, these Fc-contained MOFs usually exhibit unique performance in many fields compared with pristine MOFs and bare Fc molecules. In this review, the recent progresses of Fc-contained MOFs and their derived materials are reviewed, including the role of Fc in Fc-contained MOFs, synthesis methods and corresponding applications. The challenges and potential research directions of Fc-contained MOFs are also presented and highlighted.